Content and organization of physical education of students based on the use of dance sport tools - Zhu Yulin (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretical and experimental substantiation of the effectiveness of the model of content and organization of physical education of students using dance sport in the socio-cultural environment of the university. The authors developed a model that includes: target, conceptual and methodological, content, organizational and activity and evaluation and result blocks. The authors proposed organizational forms of educational and extracurricular activities, program and methodological support for an elective course in physical education and sports and an optional course (dance sport module and optional dance sport) in the socio-cultural environment of the university.